Financial Literacy and Investment Decisions in Nepalese Share Market - Subedi, Dhruba Prasad (Management Dynamics, 2023)
This study examines the role of financial literacy on the investment decisions of investors in the Nepalese share market. Financial literacy is expressed in personal saving, risk tolerance, investment options, and financial knowledge. The data were collected through a structured questionnaire using the convenience sampling method from 384 respondents of Kathmandu Valley. Pearson correlation and multiple regression analysis have been used to analyze data. The study results revealed a positive and significant relationship between the dimensions of financial literacy and investment decisions in the Nepalese share market. Low financial literacy and lack of financial information affect the ability to save and make sound financial decisions. Ignorance of basic financial concepts results in negative behavior in saving and investment decisions. The study suggests conducting financial education programs to help improve investors’ savings and financial decisions.